AKTA PERDAMAIAN YANG DIBUAT DIHADAPAN NOTARIS SEBAGAI DASAR PERTIMBANGAN HAKIM UNTUK MEMUTUS PERKARA DI PENGADILAN (PUTUSAN PENGADILAN TINGGI MEDAN NOMOR: 305/PDT/2015/PT-MDN) - SYARIFAH NURJANI P (PREMISE LAW JURNAL, 2017)
A dispute which costs less money and spends a little time can be settled by litigants to reconcile. The Supreme Court’s Ruling No.2/2003 on the Procedure of Mediation in the Court states that all civil cases in the District Court have to be settled through reconciliation with mediators. They can also be settled before a Notary by making Reconciliation Deeds. A Notary’s authority to make all deeds, including reconciliation ones, otherwise stipulated differently by law, is based on Article 15, paragraph 1 of Law No. 30/2004 in conjunction with on Notary’s Position in conjunction with Law No. 2/2004 on the Amendment of Law No. 30/2004 on Notary’s Position. An authentic deed made by a Notary is strong evidence needed by the related parties. The reconciliation deed can be used as evidence before the court which can be the judge’s consideration in handing down a Ruling as reconciliation in the Medan Appellate Court. The research used descriptive analytic method on Reconciliation Deed made by a Notary as the Judge’s Consideration to Hand Down a Ruling, using juridical normative approach related to Reconciliation Deed made before a Notary. The result of the research showed that Reconciliation Deed made before a Notary can be one of the alternatives in settling a dispute outside the Court with quick process and less money spent on it. It is recommended that litigants can reconcile by making a reconciliation deed before a Notary in order to settle it quickly with less money. Keywords: Reconciliation Deed, Notary, Appellate Court